A Survey Research on Feedback Practices in Agile Software Development Teams - Ribeiro, Ana Beatriz Cavalcanti; Alves, Carina Frota (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2021)
The need for greater flexibility, autonomy and dynamism in software development has increased the adoption of agile methodologies. In order to support the recommended practices of these methodologies, maintaining good communication between team members and promoting a positive work environment that allows the individual growth of employees through autonomous learning and decision making have become key success factors. In this context, feedback is an important practice to provide each employee with an analysis of their performance, both personal and technical. The objective of this paper is to investigate the impact of feedback on motivational factors from the perspective of developers, testers and managers of agile development teams. We conducted a survey with 25 collaborators to assess motivational factors and possible points for improvement in the feedback process adopted by the teams. Among the obtained results, job satisfaction and productivity were positively influenced by the practice of feedback. In contrast, the periodicity of feedback and the absence of an evaluation among members were considered improvement points. Based on the survey results, we provided a set of recommendations to improve the quality of the feedback process in agile teams.